Sistem Informasi Akuntansi Penjualan Alat Pemadam Kebakaran pada PT Sinar Surya Semestaraya - Dahlia Dahlia; Endah Wiji Lestari; Nuraeni Herlinawati; Leliyanah Leliyanah (Journal of Students‘ Research in Computer Science, 2023)
Information technology, especially in the field of computer technology, has developed very rapidly which has brought to the new world, communication plays an important role in life. Various facilities are provided to meet all communication needs, especially sales. This can be seen from the many places that provide internet facilities to obtain information, which can be enjoyed by all groups at an affordable cost. PT. Sinar Surya Semestaraya is a company that sells fire extinguishers. The sales system is still not computerized, so it is difficult to record sales transactions and manage sales reports resulting in miscalculations due to employee negligence. This is less effective and efficient, because it is difficult to record and calculate the number of types of goods that exist. The large number of items sold and the crowd of buyers can make it difficult for sellers to organize and calculate sales transactions quickly, precisely and efficiently. The solution to the problem is utilizing accounting information systems, especially the sale of fire extinguishers. Through computerization, it is hoped that it will make it easier for consumers to make the purchasing process and get complete information. Information on product names is available using a website-based sales application program. Companies can market one product to consumers with a wide range, so that from a business perspective it is a good opportunity to expand product sales marketing..  Keywords: Accounting Information,  Fire Equipment Sales, Information System, Information Technology   Abstrak Teknologi informasi khususnya bidang teknologi komputer, telah berkembang sangat pesat yang telah membawa ke dunia baru, komunikasi memegang peranan penting dalam kehidupan. Berbagai fasilitas disediakan untuk memenuhi segala kebutuhan komunikasi, khususnya penjualan. Terlihat dari banyaknya tempat yang menyediakan fasilitas internet untuk memperoleh informasi, dan dinikmati semua kalangan dengan biaya terjangkau. PT. Sinar Surya Semestaraya perusahaan yang menjual alat pemadam kebakaran. Pada sistem penjualan masih belum terkomputerisasi sehingga mengalami kesulitan pencatatan transaksi penjualan dan pengelolaan laporan penjualan mengakibatkan kesalahan perhitungan oleh kelalaian pegawai. Hal ini kurang efektif dan efisien, karena sulit mencatat dan menghitung jumlah jenis barang yang ada. Banyaknya jumlah barang yang terjual dan tingkat keramaian pembeli dapat menyulitkan penjual untuk mengatur dan menghitung transaksi penjualan secara cepat, tepat, dan efisien. Solusi dari permasalahan memanfaatkan sistem informasi akuntansi khususnya penjualan alat pemadam kebakaran. Melalui terkomputerisasi diharapkan memudahkan konsumen dalam melakukan proses pembelian dan mendapatkan informasi yang lengkap. Informasi nama-nama produk tersedia dengan menggunakan program aplikasi penjualan berbasis website. Perusahaan dapat memasarkan satu produk kepada konsumen dengan jangkauan yang luas, sehingga dari segi bisnis merupakan peluang yang baik untuk memperluas pemasaran penjualan produk. Kata kunci: Informasi Akuntansi, Penjualan Alat Kebakaran, Sistem Informasi, Teknologi Informasi